A method for efficiently removing perfluorinated compounds from wastewater
Through the combination of magnetic bifunctional fluorinated amination polycondensate spheres and ion-responsive resin microspheres, the electrostatic attraction and fluorine-fluorine interactions are used to solve the problem of low removal efficiency and insufficient selectivity of perfluorinated compounds in the prior art. The problem is that efficient and stable adsorption effect is achieved and is suitable for contaminated water treatment in complex environments.
Patent Information
- Application Number
- CN202411114943.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The prior art is not efficient when removing perfluoro compounds in wastewater, is susceptible to water environment, and lacks selectivity in adsorbent materials, making it difficult to efficiently remove perfluoro compounds in the presence of multiple coexisting anionic pollutants.
A magnetic bifunctional fluorinated aminated polycondensate sphere adsorption material and ion-responsive resin microspheres wrapped in lysine are designed to achieve selective adsorption through electrostatic attraction and fluorine-fluorine interaction, combining magnetic and ions Responsive mesoporous silicon-based polymer spheres enhance adsorption performance.
It has achieved efficient and selective removal of perfluoro compounds in wastewater, with an adsorption rate of more than 95%, and the material has stable performance after multiple recycling, making it suitable for severely contaminated water samples in complex environments.
Smart Images

Figure CN118771524B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, specifically to the technical field of removing new pollutants in water by adsorption, and in particular to a method for removing perfluorinated compounds in wastewater. Background Art
[0002] Regarding the pollution of perfluorinated compounds in wastewater, since the concentration of perfluorinated compounds in industrial wastewater is not high, if the advanced oxidation or reduction method is directly applied to degrade them, there may be problems of high energy consumption and low efficiency. Transferring pollutants from liquid phase to solid phase through adsorption treatment has the characteristics of high efficiency and easy operation. The more mature technology is to use activated carbon as an adsorbent to adsorb and remove perfluorinated compounds. However, the adsorption and removal effect of ordinary commercial activated carbon on perfluorinated compounds is limited, and the carbon layer is prone to premature penetration.
[0003] Although the C~F chains in perfluorinated compounds are hydrophobic, they have hydrophilic functional groups and usually exist in the form of anions in aqueous solutions, so they have high solubility. The C~F bond energy in perfluorinated compounds is very large, which makes perfluorinated compounds very stable and not easy to be degraded. These characteristics make perfluorinated compounds persistent and bioaccumulative in water environments, posing a potential hazard to the safety of aquatic environments. Perfluorinated compounds have similar structures, hydrophobic and oleophobic -CF long chains and hydrophilic groups -COOH and -SO3H. Due to the strong electronegativity of fluorine, the carbon-fluorine bond has a strong polarity and is one of the covalent bonds with the largest bond energy in nature. These properties make them extremely stable, and traditional chemical methods and biodegradation are difficult to apply to the removal technology of PFOA and PFOS.
[0004] The Chinese patent "An interfacial adsorption method for efficiently removing perfluorinated compounds from water" with publication number CN115321635B discloses an interfacial adsorption method for efficiently enriching perfluorinated compounds in water, wherein polluted water containing perfluorinated compounds, a long carbon chain cationic surfactant and n-hexane are mixed to obtain an oil-water mixture of an aqueous phase containing perfluorinated compounds and cationic surfactants and a n-hexane phase, and the mixture is allowed to stand for adsorption. A long carbon chain cationic surfactant is introduced at the n-hexane-water interface, so that the cationic surfactant and anionic PFCs are tightly combined through electrostatic action, thereby constructing an active interface with electron-withdrawing ability, and realizing efficient enrichment and removal of PFCs at the interface.
[0005] However, since the actual wastewater environment contains a variety of coexisting anionic organic pollutants, and the concentration is usually much higher than the concentration of perfluorinated compounds, and the oil-water mixture of the water phase and the n-hexane phase of the cationic surfactant does not have selective adsorption properties, it cannot efficiently and selectively adsorb perfluorinated compounds in the presence of many anionic pollutants in the wastewater environment. Therefore, it is necessary to develop an adsorption material that is highly selective for perfluorinated compounds.
[0006] Ordinary granular porous materials, such as commercial activated carbon, are not good at adsorbing perfluorinated compounds in water environments. Perfluorinated compounds easily form micellar structures that block micropores, resulting in decreased adsorption. Although powder materials such as powdered activated carbon and hydrotalcite have high adsorption for perfluorinated compounds, they are difficult to separate from water. Moreover, these materials are not selective and are easily affected by other coexisting impurities in actual water bodies, thus losing their adsorption capacity. Although molecular imprinting materials have been synthesized to selectively adsorb and remove perfluorinated compounds, their selectivity is not high and is easily affected by coexisting compounds with similar structures and molecular sizes.
[0007] Effective removal of perfluorinated compounds in wastewater is a hot topic in the current research field. Therefore, it is necessary to develop a method for efficiently adsorbing perfluorinated compounds in wastewater. Summary of the invention
[0008] In order to solve the above problems, a method for efficiently adsorbing perfluorinated compounds in wastewater is developed. The method uses adsorbent materials to adsorb perfluorinated compounds in wastewater. Specifically, the adsorbent material is added to the wastewater solution, the pH value of the wastewater solution is adjusted to 6-7, the temperature is controlled at 15-45°C, and the constant temperature oscillation adsorption is performed for 10-150 minutes. After reaching adsorption equilibrium, the adsorbent material particles are separated and removed.
[0009] The wastewater is chemical wastewater containing perfluorinated compounds, and the adsorbent material is a bifunctional fluorinated aminated polycondensate spherical adsorbent material, which removes perfluorinated compounds in the water by directional adsorption;
[0010] The purpose of the present invention is to provide an adsorbent material capable of adsorbing perfluorinated compounds in chemical wastewater to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.
[0011] Based on the unique oleophobic, hydrophobic and fluorine-affinity properties of the CF chain, and taking advantage of its ability to repel hydrocarbons in water but be close to perfluorinated compounds, a magnetic bifunctional fluorinated amino condensation polymer spherical adsorbent material was designed. This adsorbent can selectively adsorb and remove perfluorinated compounds in water.
[0012] First, the adsorption material is based on the condensation polymer of high molecular cross-linked nano-silicon dioxide. The preparation of the condensation polymer matrix of the high molecular cross-linked nano-silicon dioxide is as follows:
[0013] S001, in a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 3-aminopropyl triethoxysilane, dimethyl dimethoxysiloxane and dodecafluoroheptyl propyl trimethoxysilane are mixed with ethanol, stirred evenly, and deionized water is added as a reaction solvent. The mixture is stirred at room temperature for 1 hour until the solution is clear, and then diluted phosphoric acid is added dropwise, and the temperature is raised to 30-40°C for reaction for 18-20 hours. After the reaction stops, the acid-water layer is separated by standing for 60-80 minutes, and the acid-water layer is washed with water several times until it is neutral, and the small molecules and other substances remaining in the reaction system are removed, so as to obtain a condensation polymer matrix with a molecular weight of 20,000-30,000; the mass ratio of the vinyl trimethoxysiloxane, 3-aminopropyl triethoxysilane and dodecafluoroheptyl propyl trimethoxysilane is 1:3:3.
[0014] The condensation polymer with a molecular weight of 20,000 to 30,000 is preferably used as the matrix. The main reason is that if the molecular weight of the high molecular weight condensation polymer matrix is too small, the cross-linking network is insufficient and the porosity is small, so that it cannot load too many small molecular substances, which will cause its loading rate to be too low and the obtained matrix to be too dense. The molecular weight range allows more cross-linking networks and enables large particles to effectively combine with silicon and oxygen, increasing the porosity and specific surface area. Siloxanes with fluorine functional groups and amine functional groups are selected because these two functional groups have priority in the adsorption of perfluorinated compounds. Therefore, the condensation polymer matrix has suitable mesopores and has adsorption selectivity for perfluorinated compounds.
[0015] S002, nano-silicon dioxide and a condensation polymer matrix with a molecular weight of 20,000 to 30,000 are mixed in an alcohol ether solution by a solution blending method, and stirred at high speed for 60 to 90 minutes, so that the nano-silicon dioxide is fully cross-linked in the condensation polymer matrix, and a condensation polymer matrix of high molecular cross-linked nano-silicon dioxide is obtained. The mass ratio of the silicon dioxide to the condensation polymer matrix is 1:10 to 12;
[0016] The cross-linking of silicone resin utilizes the hydroxyl groups on silicon atoms to undergo shrinkage polymerization and cross-linking into a network structure, which is deeply cross-linked with nano-silicon dioxide to form a highly cross-linked high-molecular-weight cross-linked low-molecular-weight condensation polymer matrix.
[0017] S003, adding hyperbranched polyamide-amine to the condensation polymer matrix of high molecular cross-linked nano-silica, adjusting to alkalinity with a NaOH solution with a mass concentration of 0.01%, then adding 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stirring and reacting at 60-80°C for 10-12 hours, centrifuging, washing with water, and drying to obtain a silicon-oxygen polymer grafted with hyperbranched polyamide-amine; recorded as a bifunctional fluorinated aminated condensation polymer spherical adsorption material;
[0018] Under alkaline catalytic conditions, the amine groups in the hyperbranched polyamide-amine are grafted onto the condensation polymer matrix of high molecular cross-linked nano-silica, and it can be stably dispersed in water or organic solvents;
[0019] The mass ratio of the condensation polymer matrix of hyperbranched polyamide-amine, 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and high molecular cross-linked nano-silica is 2-4:1-2:15-20;
[0020] Further, it is subjected to magnetization treatment, specifically:
[0021] S101, stirring and mixing ferroferric oxide, ferric chloride and a 30% ethanol solution to obtain a mixed solution; the mass ratio of ferroferric oxide to ferric chloride is 4:1; and the total mass fraction of ferroferric oxide and ferric chloride is 10%;
[0022] S102, adding the bifunctional fluorinated aminated polycondensate spherical adsorbent material and the mixed solution in S101 into a high-pressure reactor for reaction, then adding ethylene glycol and stirring evenly, reacting at a temperature of 100-110°C for 3-5 hours, cooling to room temperature after the reaction is completed, and obtaining a suspension; using a magnet to separate the suspension to obtain a precipitate, washing the precipitate 1-3 times, and drying it at a temperature of 40-50°C to obtain a final product, which is recorded as a magnetic bifunctional fluorinated aminated polycondensate spherical adsorbent material. The mass ratio of the bifunctional fluorinated aminated polycondensate spherical adsorbent material to ferroferric oxide is 10:1.
[0023] The fluorine groups on the adsorbent material can interact with the fluorine on the CF chain of the perfluorinated compound to achieve the purpose of selective adsorption. Although the magnetic fluorinated polycondensate sphere adsorbent material can efficiently and selectively adsorb perfluorinated compounds in water, due to the strong hydrophobicity of the surface, the fluorinated material easily forms aggregates in the solution and floats on the water surface, which has a negative impact on its adsorption capacity, especially the rate. To address this problem, a magnetic adsorbent with a hydrophilic outer surface but fluorinated interlayers was prepared by ball milling to efficiently, quickly and selectively adsorb and remove perfluorinated compounds in water.
[0024] However, during wastewater treatment, it was found that in the adsorption process, since the adsorption principle uses the electrostatic attraction of positive and negative charges to carry out adsorption enrichment, when the cations of the adsorbent material are surrounded by anions in the perfluorinated compounds in the wastewater, the adsorption effect will continue to deteriorate, and ultimately no more perfluorinated compounds can be adsorbed. In order to solve the problem of continuous consumption of cations in the adsorbent material, we have designed an ion-responsive resin microsphere wrapped with amino acids. The microsphere will release lysine in the condensation polymer matrix, and lysine is positively charged in a neutral or acidic environment, so that positively charged cations are continuously released in the adsorbent material, thereby providing a continuous supply of cations in the adsorbent material.
[0025] The method for preparing the ion-responsive resin microspheres encapsulating lysine comprises the following steps:
[0026] S201: Stir butyl acrylate, dimethylaminoethyl acrylate, hydroxypropyl acrylate and n-dodecyl mercaptan evenly, slowly heat to 80-100° C. under nitrogen protection, then drop initiator tert-butyl peroxybenzoate, react for 80-150 minutes, cool to 50-60° C., add acrylic acid, and continue to react for 50-70 minutes to obtain an ion-responsive acrylic resin polymer having an average molecular weight of 1000-2000;
[0027] Furthermore, in parts by mass, butyl acrylate is used in an amount of 30 to 40 parts, acrylic acid is used in an amount of 10 to 12 parts, dimethylaminoethyl acrylate is used in an amount of 15 to 20 parts, hydroxypropyl acrylate is used in an amount of 15 to 25 parts, dodecanethiol is used in an amount of 1.5 to 2.0 parts, and tert-butyl peroxybenzoate is used in an amount of 0.5 to 1.0 parts;
[0028] A polymer obtained by free radical polymerization of acrylic acid and its ester monomers under the action of an initiator. Hydroxyl, carboxyl and amine functional groups are introduced during the preparation process, and the resulting polymer particles have a smaller diameter and a higher degree of polymerization. The molecular weight of the polymer can be controlled at 1000-2000, and the introduced functional groups can respond quickly to hydrogen ions.
[0029] S202: Add lysine and ion-responsive acrylic resin polymer to ethanol, raise the temperature to 60°C under nitrogen protection, maintain the high-speed dispersion state for 0.5 to 1.5 hours, and form an organic phase; cool to room temperature, remove ethanol at low temperature, and dry at room temperature for 72 hours to obtain ion-responsive resin microspheres encapsulating amino acids.
[0030] Furthermore, the mass ratio of lysine to ion-responsive acrylic resin polymer is 2:10-15;
[0031] Lysine is encapsulated in an acrylic resin polymer medium. During the entire release process, there are many complex physical and chemical phenomena. The reason why a carrier with a molecular weight of 1000 to 2000 is selected to carry lysine is that if the molecular weight is too large in the matrix, the microspheres will not be easy to be freed and release lysine; if the molecular weight is too small, it will not be easy to be wrapped by the polymer matrix, the loading amount will be relatively low, and in the free process, it will be easily blocked by other large molecular weight grids, thus affecting the release of lysine.
[0032] When hydrogen ions exist in the environment, the tertiary amine groups in the side chains of the ion-responsive resin microspheres undergo protonation and ester hydrolysis, which can produce positive electrical repulsion between polymer chains, thereby reducing the steric hindrance of the polymer and causing similar polymer network relaxation, thereby releasing lysine from the encapsulation. When there are hydroxide ions in the environment, its active group is -COOH. Due to the mutual repulsion of COO-, the intermolecular gap becomes larger and the structure becomes loose. At the same time, the ester group on the side chain of the ion-responsive lysine resin microsphere can also be hydrolyzed, resulting in negative electric repulsion between polymer chains, which will further cause the polymer grid structure to relax and increase the porosity, which also releases lysine. After lysine is released, because the pH value of the water environment is less than 7, and the isoelectric potential of lysine is about 9.7, in such an environment, the lysine in the matrix will continuously release hydrogen ions, and the released hydrogen ions will cause the ion-responsive resin microsphere structure to continuously release lysine, so that the adsorption material matrix can continuously provide hydrogen ions, which makes its adsorption to anionic perfluorinated compounds higher again, and the adsorption performance is significantly improved.
[0033] S203, add hyperbranched polyamide-amine to the polycondensate matrix of high molecular weight cross-linked nano-silica, adjust to alkalinity with a NaOH solution with a mass concentration of 0.01%, then add 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and stir the reaction at 60-80°C for 10-12 hours to obtain a silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, and then add ion-responsive resin microspheres encapsulating lysine to the silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, stir thoroughly, evenly disperse, centrifuge, wash with water, and dry; to obtain ion-responsive polymer spheres.
[0034] S204, adding the ion-responsive polymer sphere and the mixed solution in S101 into a high-pressure reactor for reaction, then adding ethylene glycol and stirring evenly, reacting at a temperature of 100-110°C for 3-5 hours. After the reaction is completed, cooling to room temperature to obtain a suspension; using a magnet to separate the suspension to obtain a precipitate, washing the precipitate 1-3 times, and drying it at a temperature of 40-50°C to obtain a final product, which is recorded as a magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material. The mass ratio of the ion-responsive polymer sphere to ferroferric oxide is 10:1.
[0035] Mesoporous silica-based materials, due to their special mesoporous structure, allow specific functional groups to be conveniently grafted onto their surfaces. Through specific interactions from modified functional groups, mesoporous silica-based materials have high adsorption capacity and certain selectivity after modification. Therefore, magnetic ion-responsive mesoporous silica-based polymer sphere adsorption materials can better enrich and adsorb perfluorinated compounds from water, and the numerous amine groups and fluorine groups on the surface of the material can preferentially adsorb perfluorinated compounds in wastewater treatment. Because many amine groups are positively charged after protonation, they can attract a large number of anionic perfluorinated compounds. When the water environment is weakly acidic, because the ion-responsive acrylic resin releases more positive charges, the adsorption system has more electrostatic adsorption sites, which greatly improves the adsorption performance of perfluorinated compounds. There are a large number of competing compounds and colloids in the water environment, especially in wastewater, which will compete with anionic perfluorinated compounds for adsorption sites during the adsorption process, thereby reducing the adsorption capacity of the adsorption material. Therefore, selective adsorption is crucial for removing perfluorinated compounds from wastewater environments.
[0036] Electrostatic interaction is considered to be one of the main forces for perfluorinated compound adsorption, which can be formed between anionic perfluorinated compounds and positively charged adsorbents. The high electronegativity formed by the fluorine group will produce a negatively charged shell around the perfluorinated compound molecule. Each fluorine atom has a strong electronegativity and three long electron pairs, which are believed to interact with the charged functional groups on the adsorbent surface. The tail of the perfluorinated compound molecule mainly shows a hydrophobic effect rather than a charged effect. The electrostatic effect generated by the adsorbed charged species on the adsorbent surface can also affect the adsorption of perfluorinated compounds. For example, the adsorbent carries more net negative charge after adsorbing perfluorinated compound molecules, which repel subsequent perfluorinated compounds in the solution or other perfluorinated compound anions on the adsorbent surface, thereby preventing their adsorption and affecting the surface distribution on the adsorbent. Similarly, most organic pollutants that exist in a negatively charged state can also cause electrostatic repulsion to the anionic end of perfluorinated compounds. In contrast, the responsive acrylic microspheres in the magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material group can continuously release cations in the matrix to form multiple cations. When the cations can act as bridges, the negative sites on the adsorbent surface are transferred to positive charges to electrostatically attract more perfluorinated compound anion ends, thus playing the role of a bridge.
[0037] Compared with the prior art, the invention has the following beneficial effects:
[0038] 1) The present invention aims at the defects of various adsorption methods in the prior art, such as low adsorption efficiency, susceptibility to water interference, and easy to cause secondary pollution. An ion response system is constructed to form multiple active sites with electron-withdrawing ability, so as to achieve the effect of efficient and directional adsorption of perfluorinated compounds, fully stimulate electrostatic action, pore filling, hydrophobic action, fluorine-fluorine similar attraction and other adsorption mechanisms, so that the adsorption system has more electrostatic adsorption sites, greatly improving the adsorption performance of perfluorinated compounds. There are a large number of competing compounds and colloids in the water environment, especially in wastewater, to avoid competing with anionic perfluorinated compounds for adsorption sites during the adsorption process. It has high removal efficiency for perfluorinated compounds in various anionic organic co-contamination in heavily polluted water samples, especially solving the problem of low adsorption rate caused by the same-sex repulsion between adsorbed perfluorinated compounds during the adsorption process. It is very suitable for efficient removal of various co-contaminated perfluorinated compounds in heavily polluted water samples. The system can achieve efficient removal of perfluorinated compounds under complex environmental background values and has good application prospects. It provides a treatment solution for actual composite polluted water bodies.
[0039] 2) The present invention also provides a novel preparation method for adsorbing perfluorinated compounds in wastewater. A preparation method for an adsorbent material that takes into account both charge and excellent pore structure is provided. The prepared magnetic bifunctional fluorinated aminated condensation polymer sphere adsorbent material is a reticular polymer compound with functional groups, which can selectively adsorb perfluorinated compounds, has strong anti-pollution ability, high mechanical strength, good stability and can be recycled. The magnetic ion-responsive mesoporous silica-based polymer sphere adsorbent material is further improved on the basis of the magnetic bifunctional fluorinated aminated condensation polymer sphere, and the continuous adsorption performance is enhanced. Under the interference of a large number of anionic pollutants in wastewater, the ability to selectively and efficiently adsorb perfluorinated compounds in wastewater can be further improved. At the same time, a large number of ion-responsive resin microspheres encapsulating lysine are uniformly dispersed in the group of the magnetic ion-responsive mesoporous silica-based polymer sphere adsorbent material, so that the surface and interior of the material are rich in positively charged cations, which enhances the adsorption of negatively charged perfluorinated compounds. There are also a large number of amine and fluorine bifunctional groups on the surface, which significantly increases the selection and adsorption capacity of perfluorinated compounds in wastewater.
[0040] 3) This method is a green, mild and simple method that can reach adsorption equilibrium in a short time; and in this adsorption system, the efficient removal of perfluorinated compounds is guaranteed, and the adsorption rate can reach more than 95%. The adsorption material prepared by this method contains magnetic nanoparticles, which makes it possible to use magnetism to quickly separate the target analyte from the wastewater during the pretreatment of the sample to be adsorbed and separated, making the operation of adsorption and separation simple and easy. The adsorption material of the present invention shows excellent recycling performance. The adsorbed perfluorinated compounds can be efficiently eluted with methanol, and the perfluorinated compounds can be recovered and recycled by solvent concentration. In addition, after 5 adsorption-elution cycles, the overall adsorption amount of perfluorinated compounds by the material of the present invention is still more than 92% of the initial adsorption amount, indicating that after multiple cycles of use, the adsorption performance of the adsorption material is stable and the removal rate of perfluorinated compounds in wastewater is stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 , the adsorption equilibrium curve of the adsorbent material in Example 2 for perfluorinated compounds in water;
[0042] Figure 2 , electron microscope image of the magnetic ion responsive mesoporous silica-based polymer sphere adsorption material in Example 2;
[0043] Figure 3 , the effect diagram of the adsorption rate of the magnetic ion responsive mesoporous silica-based polymer sphere adsorption material on perfluorinated compounds in Example 2;
[0044] Figure 4, a diagram showing the effect of the adsorption rate of perfluorinated compounds on the magnetic ion responsive mesoporous silica-based polymer sphere adsorption material after regeneration in Example 2; DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0046] Example 1
[0047] A method for efficiently removing perfluorinated compounds from wastewater comprises the following steps: firstly preparing a bifunctional fluorinated aminated polycondensation spherical adsorption material to selectively adsorb and remove perfluorinated compounds from water;
[0048] The bifunctional fluorinated aminated condensation polymer spherical adsorption material is based on the condensation polymer of high molecular weight cross-linked nano-silica. First, a condensation polymer matrix of high molecular weight cross-linked nano-silica is prepared.
[0049] In a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, 6 parts of 3-aminopropyltriethoxysilane, 2 parts of dimethyldimethoxysiloxane, and 6 parts of dodecafluoroheptylpropyltrimethoxysilane are mixed with 20 parts of ethanol, stirred evenly, 50 parts of deionized water are added as a reaction solvent, stirred at room temperature for 1 hour until the solution is clear, and then 1 part of dilute phosphoric acid is added dropwise, and the temperature is raised to 40°C to react for 20 hours; after the reaction stops, the acid-water layer is separated by standing for 80 minutes, and the residual small molecular substances in the reaction system are removed by washing with water several times until neutral, and the polycondensate matrix with a molecular weight of 24187 is obtained;
[0050] 2 parts of nano-silica and 20 parts of condensation polymer matrix are mixed in an alcohol ether solution by a solution blending method, and stirred at high speed for 90 minutes, so that the nano-silica is also fully cross-linked in the condensation polymer matrix, and a condensation polymer matrix of high molecular cross-linked nano-silica is obtained;
[0051] Add 2 parts of hyperbranched polyamide-amine to 15 parts of the condensation polymer matrix of high molecular weight cross-linked nano-silica, adjust the pH to 8.5 with a NaOH solution with a mass concentration of 0.01%, then add 2 parts of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir and react at 80°C for 12 hours, centrifuge, wash with water, and dry to obtain a silicon-oxygen polymer grafted with a hyperbranched polyamide-amine, which is a bifunctional fluorinated amino condensation polymer spherical adsorption material.
[0052] Further, the bifunctional fluorinated aminated polycondensate spherical adsorption material is subjected to a magnetization treatment, specifically:
[0053] 8 parts of ferrosoferric oxide, 2 parts of ferric chloride and 20 parts of 30% ethanol solution by mass were stirred and mixed to obtain a mixed solution; 40 parts of bifunctional fluorinated aminated condensation polymer spherical adsorption material and 50 parts of the mixed solution were added into a high-pressure reactor for reaction, and then ethylene glycol was added and stirred evenly. The reaction time was 3 hours at a temperature of 110°C. After the reaction was completed, the suspension was cooled to room temperature to obtain a suspension; the suspension was separated by a magnet to obtain a precipitate, the precipitate was washed 3 times, and dried at a temperature of 50°C to obtain a final product, namely, a magnetic bifunctional fluorinated aminated condensation polymer spherical adsorption material.
[0054] Example 2
[0055] A method for efficiently removing perfluorinated compounds from wastewater comprises the following steps: firstly preparing an ion-responsive mesoporous silica-based polymer sphere adsorption material.
[0056] An ion-responsive resin microsphere encapsulating lysine is prepared, specifically:
[0057] 30 parts of butyl acrylate, 15 parts of dimethylaminoethyl acrylate, 25 parts of hydroxypropyl acrylate and 1.5 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 100°C under nitrogen protection, and then 1 part of initiator tert-butyl peroxybenzoate was added dropwise. After fully reacting for 150 minutes, the temperature was lowered to 60°C, 10 parts of acrylic acid were added, and the reaction was continued for 70 minutes to obtain an ion-responsive acrylic resin polymer with an average molecular weight of 1219;
[0058] 4 parts of lysine and 20 parts of ion-responsive acrylic resin polymer were added to 50 parts of ethanol, and the temperature was raised to 60°C under nitrogen protection, and the high-speed dispersion state was maintained for 1.5 hours to form an organic phase; the temperature was lowered to room temperature, the ethanol was removed at low temperature, and the mixture was dried at room temperature for 72 hours to obtain ion-responsive resin microspheres encapsulating amino acids;
[0059] Next, a polymer cross-linked nano-silica condensation polymer matrix is prepared, specifically:
[0060] In a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 6 parts of 3-aminopropyltriethoxysilane, 2 parts of dimethyldimethoxysiloxane, and 6 parts of dodecafluoroheptylpropyltrimethoxysilane are mixed with 20 parts of ethanol, stirred evenly, 50 parts of deionized water are added as a reaction solvent, stirred at room temperature for 1 hour until the solution is clear, and then 1 part of dilute phosphoric acid is added dropwise, and the temperature is raised to 40°C to react for 18 hours; after the reaction stops, the acid-water layer is separated by standing for 80 minutes, and the residual small molecular substances in the reaction system are removed by washing with water several times until neutral, and the polycondensate matrix with a molecular weight of 26035 is obtained;
[0061] 2 parts of nano-silica and 20 parts of condensation polymer matrix are mixed in an alcohol ether solution by a solution blending method, and stirred at high speed for 90 minutes, so that the nano-silica is also fully cross-linked in the condensation polymer matrix, and a condensation polymer matrix of high molecular cross-linked nano-silica is obtained;
[0062] Add 2 parts of hyperbranched polyamide-amine to 15 parts of the condensation polymer matrix of high molecular weight cross-linked nano-silica, adjust the pH to 8.5 with a NaOH solution with a mass concentration of 0.01%, then add 2 parts of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir and react at 80°C for 12 hours to obtain a silicon-oxygen polymer grafted with a hyperbranched polyamide-amine, and then add the ion-responsive resin microspheres wrapped with amino acids to the silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, stir thoroughly, evenly disperse, centrifuge, wash with water, and dry to obtain an ion-responsive polymer sphere;
[0063] 8 parts of ferroferric oxide, 2 parts of ferric chloride and 20 parts of 30% by mass ethanol solution were stirred and mixed to obtain a mixed solution;
[0064] 40 parts of ion-responsive polymer spheres and 50 parts of the mixed solution were added into a high-pressure reactor for reaction, and then ethylene glycol was added and stirred evenly. The reaction time was 5 hours at a temperature of 110°C. After the reaction was completed, the suspension was cooled to room temperature to obtain a suspension. The suspension was separated by a magnet to obtain a precipitate. The precipitate was washed 3 times and dried at a temperature of 50°C to obtain a final product, namely, a magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material.
[0065] Example 3
[0066] A method for efficiently removing perfluorinated compounds from wastewater comprises the following steps: firstly preparing an ion-responsive mesoporous silica-based polymer sphere adsorption material.
[0067] An ion-responsive resin microsphere encapsulating lysine is prepared, specifically:
[0068] 40 parts of butyl acrylate, 20 parts of dimethylaminoethyl acrylate, 15 parts of hydroxypropyl acrylate, and 2.0 parts of n-dodecyl mercaptan were stirred evenly, and the temperature was slowly raised to 100°C under nitrogen protection, and then 0.5 parts of initiator tert-butyl peroxybenzoate was added dropwise. After fully reacting for 150 minutes, the temperature was lowered to 60°C, 12 parts of acrylic acid were added, and the reaction was continued for 70 minutes to obtain an ion-responsive acrylic resin polymer with an average molecular weight of 1876;
[0069] 4 parts of lysine and 30 parts of ion-responsive acrylic resin polymer were added to 50 parts of ethanol, and the temperature was raised to 60°C under nitrogen protection, and the high-speed dispersion state was maintained for 1.5 hours to form an organic phase; the temperature was lowered to room temperature, the ethanol was removed at low temperature, and the mixture was dried at room temperature for 72 hours to obtain ion-responsive resin microspheres encapsulating amino acids;
[0070] Next, a polymer cross-linked nano-silica condensation polymer matrix is prepared, specifically:
[0071] In a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, 6 parts of 3-aminopropyltriethoxysilane, 2 parts of dimethyldimethoxysiloxane, and 6 parts of dodecafluoroheptylpropyltrimethoxysilane are mixed with 20 parts of ethanol, stirred evenly, 50 parts of deionized water are added as a reaction solvent, stirred at room temperature for 1 hour until the solution is clear, and then 1 part of dilute phosphoric acid is added dropwise, and the temperature is raised to 40°C to react for 18 hours; after the reaction stops, the acid-water layer is separated by standing for 80 minutes, and the residual small molecular substances in the reaction system are removed by washing with water several times until neutral, and the polycondensate matrix with a molecular weight of 29121 is obtained;
[0072] 2 parts of nano-silicon dioxide and 24 parts of condensation polymer matrix are mixed in an alcohol ether solution by a solution blending method, and stirred at high speed for 90 minutes, so that the nano-silicon dioxide is fully cross-linked in the condensation polymer matrix, and a condensation polymer matrix of high molecular cross-linked nano-silicon dioxide is obtained;
[0073] 4 parts of hyperbranched polyamide-amine are added to 20 parts of the condensation polymer matrix of high molecular weight cross-linked nano-silica, and the pH is adjusted to 8.5 with a NaOH solution with a mass concentration of 0.01%, and then 1 part of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is added, and the reaction is stirred at 80° C. for 12 hours to obtain a silicon-oxygen polymer grafted with a hyperbranched polyamide-amine, and then the ion-responsive resin microspheres encapsulating lysine are added to the silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, and the mixture is fully stirred, uniformly dispersed, centrifuged, washed with water, and dried to obtain ion-responsive polymer spheres;
[0074] 8 parts of ferroferric oxide, 2 parts of ferric chloride and 20 parts of 30% by mass ethanol solution were stirred and mixed to obtain a mixed solution;
[0075] 40 parts of ion-responsive polymer spheres and 50 parts of the mixed solution were added into a high-pressure reactor for reaction, and then ethylene glycol was added and stirred evenly. The reaction time was 5 hours at a temperature of 110°C. After the reaction was completed, the suspension was cooled to room temperature to obtain a suspension. The suspension was separated by a magnet to obtain a precipitate. The precipitate was washed 3 times and dried at a temperature of 50°C to obtain a final product, namely, a magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material.
[0076] Comparative Example 1, without adding hyperbranched polyamidoamine and 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to the amination treatment, and the rest is the same as in Example 2;
[0077] Comparative Example 2, without adding hyperbranched polyamidoamine and 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and without adding ion-responsive resin microspheres encapsulating lysine, and other aspects are the same as those of Example 2;
[0078] Comparative Example 3, the adsorbent material in Example 1 of an adsorbent material for adsorbing perfluorinated compounds in water disclosed in Chinese Patent Publication No. CN111330542B;
[0079] Experimental effect comparison data
[0080] 1. Particle size distribution and specific surface area of adsorption materials
[0081] The particle size distribution of the adsorbent material in the water body can be measured by a particle size analyzer. The measurement steps are as follows: take 1L of tap water and place it in the sample pool of the particle size analyzer, start the measurement program at a speed of 3000 r / min, first measure the background value, add the sample to be tested to the 1L sample pool, and stop adding the sample to be tested until the instrument reaches the set concentration value of effective particles, and obtain a particle size distribution diagram; according to the above method, use a particle size analyzer to analyze Examples 1-3 and Comparative Examples 1-3, and obtain the corresponding particle size distribution of the adsorbent material, see Table 1;
[0082] The static nitrogen adsorption method is a common method for determining specific surface area. The principle is to observe the adsorption and desorption of nitrogen by the sample under vacuum conditions, and use a mathematical model to calculate the specific surface area and pore size distribution of the sample. The total specific surface area of the adsorbent material is also calculated. In the JW-BK200C specific surface area and pore size analyzer, the adsorbent material is first vacuum degassed at 200°C for 8 hours, and then the adsorbent material samples in Examples 1-3 and Comparative Examples 1-3 are tested at liquid nitrogen temperature to obtain the specific surface area (m 2 / g) and porosity (%); see Table 1
[0083] Table 1 Particle size distribution and specific surface area of adsorption materials
[0084]
[0085] From Table 1, the diameters of Examples 1-3 and Comparative Examples 1-2 are relatively uniform. Because the ion-responsive resin microspheres encapsulating amino acids are used in Examples 2-3 and Comparative Example 1, the particle sizes obtained are larger. Also, because the microspheres are dispersed in the matrix, the specific surface area and porosity of the adsorbent material are larger than those of Example 1 and Comparative Example 2 without microspheres, which is more conducive to the adsorption of perfluorinated compounds in water. Comparative Example 3 has a large particle size range due to the crushing of the adsorbent material, but the adsorbent material has a very good specific surface area and porosity.
[0086] 2. Electron microscopy images of magnetic ion-responsive mesoporous silica-based polymer sphere adsorption materials
[0087] The morphology of the adsorbent material was observed using a field emission scanning electron microscope Nova NanoSEM450 from FEI. Before the test, the magnetic ion responsive mesoporous silica-based polymer sphere adsorbent material sample in Example 2 was evenly dispersed on the conductive glue, and the scanning electron microscope parameters were adjusted to set the acceleration voltage, detection current 10mA, resolution 1.7nm, and magnification 1000 times; the morphology is shown in Figure 2 ,from Figure 2 It can be seen that the adsorption material is a spherical microporous structure with small size and relatively uniform dispersion. It has a three-dimensional porous structure. The pore wall is composed of large molecular silicon oxides. This special morphology structure has a high specific surface area and a large number of active sites, and can selectively and efficiently adsorb perfluorinated compounds in wastewater.
[0088] 3. Effect of anions on adsorption performance
[0089] Because the concentration of perfluorinated compounds in actual wastewater is very low, and there are various interferences from other anions, which will greatly reduce the adsorption of perfluorinated compounds by the adsorbent material, in order to examine the adsorption capacity of the adsorbent material for interfering anions and verify the selectivity of the adsorbent material for perfluorinated compounds, a 10.0 mg / L perfluorinated compound solution containing PFOS and PFOA was prepared. PFOS is perfluorooctane sulfonate, and PFOA is perfluorooctane carboxylate. The solution also contains 100 mg / L of Cl - and 200mg / L SO4 2- 1000 mL of the solution was measured, the pH was adjusted to 6, and 0.5 g of the adsorption materials of Examples 1-3 and Comparative Examples 1-3 were added at room temperature, respectively, and the mixture was placed in a shaker and shaken at a speed of 150 rpm. Samples were taken at 5 minutes, 10 minutes and 30 minutes, respectively, and the concentration of each substance was tested. The adsorption rate was calculated and shown in Table 2;
[0090] Table 2 Record of adsorption rate of various anions by adsorbent materials
[0091]
[0092] As can be seen from Table 2, although the magnetic bifunctional fluorinated aminated polycondensate spherical adsorption material of Example 1 can directionally adsorb perfluoro compounds, due to the presence of a large number of anions in the solution, a large amount of electrostatic repulsion is generated during the adsorption process, and more perfluoro compounds cannot be adsorbed. The magnetic ion-responsive mesoporous silicon-based polymer spherical adsorption material of Examples 2-3 contains resin microspheres that release positive charges, so that multiple active potential centers appear in the adsorption material, which significantly enhances the ability to directionally adsorb perfluoro compounds. However, due to the increase in the active positive charges released, the adsorption amount of other anions also increases slightly, but does not interfere with the adsorption amount of perfluoro compounds. Comparative Example 1 does not add hyperbranched polyamide-amine, so that the bifunctional group adsorption material lacks aminated functional groups, thereby significantly reducing the ability to directionally adsorb perfluoro compounds. However, the addition of resin microspheres that release positive charges causes multiple active potential centers to appear in the adsorption material, which dramatically increases the adsorption capacity for other anions. This is because a large number of active points appear in the adsorption material. Due to the effect of positive and negative charges, Cl - and SO4 2- Other anionic substances are captured in large quantities. However, the adsorption material of Comparative Example 3 has no selectivity, so it is not selective for perfluorinated compounds, Cl - and SO4 2- The adsorption orientation is almost the same and is carried out simultaneously.
[0093] It can also be seen from the data in Table 3 that Cl - and SO4 2- All of them have a certain inhibitory effect on the adsorption performance of the adsorption material, forming a competitive behavior with perfluorinated compounds, and SO4 2- Cl - When the adsorption sites of the adsorbent material are limited, the presence of coexisting anions prevents the adsorption of perfluorinated compounds, and SO4 2- The end of SO4 is similar to the sulfonic acid group structure of perfluorinated compounds, so 2- When the adsorbent material has fluorine and amine dual functional groups, it can significantly overcome this competitive adsorption and show preferential adsorption of perfluorinated compounds.
[0094] 4. Adsorption equilibrium and adsorption rate
[0095] Since PFOS and PFOA in actual industrial wastewater are within a certain range, the ion-responsive mesoporous silica-based polymer sphere adsorption material of Example 2 was subjected to an adsorption experiment. The concentration gradient of 1.0, 10, and 100 mg / LPFOS and PFOA solutions were prepared. 1000 mL of solution was measured and appropriate amounts of adsorbent were added: 0.1 g, 0.2 g, and 0.5 g, respectively. The solution was placed in a shaker at room temperature with a shaker speed of 150 rpm. The sampling time was 1 hour. The adsorption rate of perfluorinated compounds was as follows: Figure 3 It can be seen that at different initial concentrations, the adsorption rate of the adsorbent material for perfluorinated compounds can reach more than 98%. And to the initial concentration of 100 mg / LPFOS and PFOA solution, 0.5g of the adsorbent materials involved in Examples 1-3 and Comparative Examples 1-3 were added respectively, and the adsorption rate of perfluorinated compounds within one hour was recorded, as shown in Table 4;
[0096] Table 4 Adsorption rate record of adsorption materials
[0097]
[0098] At the same time, the equilibrium test of the maximum adsorption amount of high concentration perfluorinated compounds was carried out. The initial concentration of PFOS and PFOA aqueous solution was 400 mg / L, the pH value of the solution was 6, the temperature was controlled at 25°C, and the constant temperature oscillation adsorption was performed for 50 minutes. The adsorption amount of PFOS and PFOA by the ion-responsive mesoporous silica-based polymer sphere adsorption material of Example 2 changed with time. Figure 1 The horizontal axis is the adsorption time, and the vertical axis is the adsorption amount of perfluorinated compounds by the ion-responsive mesoporous silica-based polymer sphere adsorption material. Figure 1 It can be seen that the adsorption of PFOS and PFOA by the ion-responsive mesoporous silica-based polymer sphere adsorbent material can basically reach saturated adsorption in about 20 minutes, which are 352 mg / g and 292 mg / g respectively. Therefore, the ion-responsive mesoporous silica-based polymer sphere adsorbent material not only has excellent adsorption capacity for PFOS, but also significantly improves the capture capacity of PFOS, achieving very good adsorption capacity.
[0099] This is because under weak acid conditions, after the magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material sample adsorbed negatively charged perfluorinated compounds, stronger electrostatic repulsion occurred between anions. At this time, due to the effect of hydrogen ions, the ion-responsive resin microspheres wrapped with amino acids in the adsorption material released positive charges at more active sites due to weak acidity under weak acid conditions. At this time, the multiple active sites of positive charges added by the adsorption material became the center, alleviating the electrostatic repulsion of the environment and further enhancing the adsorption. Therefore, Figure 1It can be seen from the figure that the curve shows that the adsorption speed slows down first, and then the adsorption capacity increases with the increase of time.
[0100] 5. Renewable performance of adsorption materials
[0101] The desorption experiment was carried out with the amine-based adsorption material, and the perfluorinated compounds in the water were enriched by adsorption-desorption operation, and then the subsequent chemical treatment was carried out. For the adsorption material of Example 2, the adsorbed material was collected by a magnet, a certain volume of desorption liquid was added, and the pH was adjusted with a NaOH solution. After being placed on a shaker at a speed of 150r / min for a certain period of time, the supernatant was taken and diluted and then tested to obtain the adsorption amount of the material.
[0102] 1 g of the adsorbent material of Example 2 was added to 1 L of a PFOS solution with an initial concentration of 250 mg / L and a PFOA solution with an initial concentration of 200 mg / L, respectively, and shaken at 170 rpm in a shaker for 48 hours. The concentrations of PFOS and PFOA in the adsorbed solutions were analyzed by HPLC-MS / MS.
[0103] After filtering the saturated adsorbent material, place it in an amine-based adsorbent material for desorption experiment and regeneration for 12 hours. The regenerated adsorbent material is put into the PFOS and PFOA solution again for the second round of adsorption. This adsorption regeneration experiment is repeated 5 times. Figure 4 ,from Figure 4 The experimental results show that the adsorption amount of PFOS and PFOA by the magnetic ion responsive mesoporous silica-based polymer sphere adsorption material remains unchanged after repeated use. The adsorption amount of PFOS by the magnetic ion responsive mesoporous silica-based polymer sphere adsorption material is about 245 mg / g, and the adsorption amount of PFOS is about 192 mg / g.
[0104] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.
Claims
1. A method for efficiently removing perfluorinated compounds from wastewater, characterized in that: Adsorbing perfluorinated compounds in wastewater using adsorbent materials, specifically: adding adsorbent materials to wastewater solution, adjusting the pH value of wastewater solution to 6-7, controlling the temperature at 15-45°C, adsorbing at constant temperature and oscillating for 10-150 minutes, and separating and removing adsorbent material particles after reaching adsorption equilibrium; The wastewater is chemical wastewater containing perfluorinated compounds, and the adsorbent material is a magnetic ion-responsive mesoporous silicon-based polymer sphere adsorbent material that removes perfluorinated compounds in the wastewater by directional adsorption; S001, in a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 3-aminopropyltriethoxysilane, dimethyldimethoxysiloxane and dodecafluoroheptylpropyltrimethoxysilane are mixed with ethanol, stirred evenly, deionized water is added as a reaction solvent, stirred at room temperature for 1 hour until the solution is clear, and then diluted phosphoric acid is added dropwise, and the temperature is raised to 30-40°C to react for 18-20 hours; after the reaction stops, the acid-water layer is separated by standing for 60-80 minutes, and the residual small molecular substances in the reaction system are removed after multiple water washing until neutral, and the polycondensate matrix with a molecular weight of 20000-30000 is obtained; S002, mixing nano-silica with a condensation polymer matrix with a molecular weight of 20,000 to 30,000 in an alcohol ether solution by a solution blending method, stirring at high speed for 60 to 90 minutes, so that the nano-silica is also fully cross-linked in the condensation polymer matrix, to obtain a condensation polymer matrix of high molecular cross-linked nano-silica; S201, butyl acrylate, dimethylaminoethyl acrylate, hydroxypropyl acrylate, and n-dodecyl mercaptan are uniformly stirred, and the temperature is slowly raised to 80-100° C. under nitrogen protection, and then tert-butyl peroxybenzoate as an initiator is added dropwise, and after fully reacting for 80-150 minutes, the temperature is lowered to 50-60° C., acrylic acid is added, and the reaction is continued for 50-70 minutes to obtain an ion-responsive acrylic resin polymer having an average molecular weight of 1000-2000; In terms of mass, the amount of butyl acrylate is 30-40 parts, acrylic acid is 10-12 parts, dimethylaminoethyl acrylate is 15-20 parts, hydroxypropyl acrylate is 15-25 parts, dodecanethiol is 1.5-2.0 parts, and tert-butyl peroxybenzoate is 0.5-1.0 parts; S202, adding lysine and ion-responsive acrylic resin polymer to ethanol, raising the temperature to 60° C. under nitrogen protection, maintaining a high-speed dispersion state for 0.5 to 1.5 hours, and forming an organic phase; cooling to room temperature, removing ethanol at low temperature, and drying at room temperature for 72 hours to obtain ion-responsive resin microspheres encapsulating amino acids; Wherein, the mass ratio of lysine to ion-responsive acrylic resin polymer is 2:10-15; S203, adding hyperbranched polyamide-amine to the polycondensate matrix of high molecular weight cross-linked nano-silica, adjusting to alkalinity with a NaOH solution having a mass concentration of 0.01%, then adding 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stirring and reacting at 60-80° C. for 10-12 hours to obtain a silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, and then adding ion-responsive resin microspheres encapsulating amino acids to the silicon-oxygen polymer grafted with the hyperbranched polyamide-amine, stirring sufficiently, evenly dispersing, centrifuging, washing with water, and drying to obtain ion-responsive polymer spheres; S204, adding the ion-responsive polymer sphere and the magnetized mixed liquid into a high-pressure reactor for reaction, then adding ethylene glycol and stirring evenly, reacting at a temperature of 100-110° C. for 3-5 hours, and cooling to room temperature after the reaction is completed to obtain a suspension; separating the suspension using a magnet to obtain a precipitate, washing the precipitate 1-3 times, and drying it at a temperature of 40-50° C. to obtain a final product, which is recorded as a magnetic ion-responsive mesoporous silica-based polymer sphere adsorption material, and the mass ratio of the ion-responsive polymer sphere to ferroferric oxide is 10:1; The magnetized mixed liquid is specifically: S101, stirring and mixing ferroferric oxide, ferric chloride and 30% ethanol solution to obtain a mixed solution; the mass ratio of ferroferric oxide to ferric chloride is 4:1; and the total mass fraction of ferroferric oxide and ferric chloride is 10%.
2. The method for efficiently removing perfluorinated compounds from wastewater according to claim 1, characterized in that: in, The mass ratio of dimethyldimethoxysiloxane, 3-aminopropyltriethoxysilane and dodecafluoroheptylpropyltrimethoxysilane is 1:3:3; The mass ratio of nano-silica to the polycondensate matrix is 1:10-12; the mass ratio of the polycondensate matrix of hyperbranched polyamide-amine, 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and high molecular cross-linked nano-silica is 2-4:1-2:15-20.
3. The method for efficiently removing perfluorinated compounds from wastewater according to claim 1, characterized in that: The perfluorinated compound is at least one of perfluorinated carboxylic acid or perfluorinated sulfonic acid.
Citation Information
Patent Citations
An adsorbent material for adsorbing perfluorinated compounds in water.
CN111330542B
An efficient interfacial adsorption method for removing perfluorinated compounds from water.
CN115321635B
Silica particles coated with beta-cyclodextrin for the removal of emerging contaminants from wastewater
CA2888213A1
Magnetic nano composite capable of absorbing perfluorochemicals and preparation method thereof
CN104492378A
Functionalized silicon dioxide modified defluorination material as well as preparation and application thereof
CN112777672A
